Peraturan Hukum Adat Baduy dan Hierarki Menurut Undang Undang yang Berlaku - Maghfiroh, Putri Azzahra (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2021)
The Baduy tribe is located closest to the capital city of the country. This is special to describe, how Baduy maintains its customs and customary laws in the midst of the influence of technological advances and the development of positive Indonesian law which is especially due to its geographical location not far from the metropolitan city, namely Jakarta and its surroundings. Then the purpose of this study also wants to reveal how Baduy customary law regulations and hierarchy according to applicable laws. Baduy is an ethnic indigenous people who still live in Indonesia. The hierarchy or order of laws and regulations in Indonesia refers to the recognition and respect given by the state in Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia, which is not sufficient to protect the rights of the Baduy customary law community plus the weakness of Perda No.32 of 2001 which discuss the customary rights of the Baduy customary community only. The clash of Baduy traditional interests with the government system has made Baduy weaker in terms of representation. The government must immediately draft a law related to the protection of Baduy customary rights and or create a representation mechanism for indigenous peoples.